Appropriate Use Criteria for Treatment of Pediatric Supracondylar Humerus Fractures With Vascular Injury: Do Our Hospital Practice Patterns Agree With Current Recommendations?. Issue 10 (November 2020) - Brandt, Aaron M.; Wally, Meghan K.; Casey, Virginia F.; Clark, Christian C.; Paloski, Michael D.; Scannell, Brian P.; Brighton, Brian K.
Abstract : Background: Managing the pulseless pediatric supracondylar humerus fracture (PSHF) remains a significant clinical decision-making challenge for the treating surgeon. The purpose of the study is to determine frequency of the treatments according to the American Academy of Orthopaedic Surgeons (AAOS) Appropriate Use Criteria (AUC) for the PSHF with vascular injury and evaluate the appropriateness of these interventions. Methods: We identified all PSHF with concern for vascular injury at one high volume, level 1 trauma center managed by 6 fellowship-trained pediatric orthopaedic surgeons over 4.5 years. Demographic information and other injury and treatment variables were obtained. Each patient was classified as 1 of the 6 patient scenarios specified by the AAOS AUC. Each of the 18 interventions identified in the AUC were documented, including the level of "appropriateness" as specified by AAOS AUC. Results: A total of 638 PSHF were managed identified; of these, 52 were pink, pulseless, or dysvascular (8.2%). Only 7 of the 18 treatment options suggested by the AUC were used in this cohort. Across all 7 interventions used in this cohort, 20.2% (17/84) of interventions were "appropriate, " 52.4% (44/84) were "maybe appropriate, " 22.6% (19/84) were "rarely appropriate, " and 4.8% (4/84) were not listed in treatment options. Conclusions: Supracondylar fractures are the most common injury to the elbow seen in children and are variable in presentation and management. The pink, pulseless fracture continues to be a major topic for research and discussion due to the morbidity if not treated "appropriately." The AUC were created to help guide practitioners when strong evidence is lacking. In this study at a single, pediatric hospital, there was variation and disagreement with "appropriateness" of treatments that were performed but this discrepancy did not result in any poor outcomes. Although the AUC do offer valuable guidance, our findings highlight a need for continued research in this area to help validate the AUC and help strengthen the recommendations moving forward. Level of Evidence: Level III—retrospective.